2012
DOI: 10.1136/vr.100449
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of Cavalier King Charles spaniel dogs with clinical signs associated with Chiari‐like malformation and syringomyelia

Abstract: The disease complex Chiari-like malformation (CM) and syringomyelia (SM) has been associated with the development of neuropathic pain (NeP), and commonly affects Cavalier King Charles spaniels (CKCS). This prospective cohort study followed 48 CKCSs with CM and/or SM and clinical signs suggestive of NeP for a period of 39 (±14.3) months from diagnosis. At the end of the study, 36 dogs were still alive; five dogs died of an unrelated or unknown cause, and seven were euthanased due to severe clinical signs sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 38 publications
4
61
0
Order By: Relevance
“…62 Along with published clinical case reports in animals, the data suggest a strong rationale for using gabapentin in dogs and cats with similar conditions. 63,64 one canine study suggested a diseasemodifying effect in experimental DJD, but clinical studies are lacking. 65 in cats, one unpublished study demonstrated a benefit of gabapentin in naturally occurring DJD (E Troncy 2013), and one case series of chronic musculoskeletal pain has also been published.…”
Section: Gabapentinmentioning
confidence: 99%
“…62 Along with published clinical case reports in animals, the data suggest a strong rationale for using gabapentin in dogs and cats with similar conditions. 63,64 one canine study suggested a diseasemodifying effect in experimental DJD, but clinical studies are lacking. 65 in cats, one unpublished study demonstrated a benefit of gabapentin in naturally occurring DJD (E Troncy 2013), and one case series of chronic musculoskeletal pain has also been published.…”
Section: Gabapentinmentioning
confidence: 99%
“…SM is a progressive disease in CKCS Plessas et al, 2012). The severities of clinical signs and clinical progression are correlated with the size of the syrinx (Rusbridge et al, 2007).…”
mentioning
confidence: 98%
“…However, the mechanism by which omeprazole affects CSF production was not elucidated in these studies. Moreover, despite the fact that both studies only focused on the immediate effect of IV or VC administration of omeprazole on CSF production, oral administration (0.5-1.5 mg/kg/day) is currently recommended for the long-term management of dogs with hydrocephalus or syringomyelia (Rusbridge et al, 2006;Thomas, 2010;Plessas et al, 2012).…”
Section: Introductionmentioning
confidence: 99%